FUNDAMENTAL STUDY ON MODIFICATION PROCESS OF DESIGN PLAN FOR COMPUTER-AIDED PRODUCT DESIGN CONSIDERING WAYS OF USAGE - Morinaga, E.; Wakamatsu, H.; Goto, Y.; Arai, E. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
Globalization in industry has increased the number of troubles caused by using products in unexpected ways. It is important to avoid such troubles in advance by performing product design considering various ways of usage. To achieve this, it is necessary to predict various ways of usage, to detect troubles which may occur by using the product in those ways and to modify the current design plan so that those troubles are avoided. A set of methods are developed based on Petri net modeling of design plan for computer support of the former two processes. The last process basically depends on creativity and knowledge of designers. However, if there are patterns of modification, it would be possible to help designers to modify design plans with computers by exploiting those patterns. This research aims at finding patterns of modification from cases of modification of design plan in actual design. Definition of pattern of modification was discussed and given as a combination of the reason, the objective and the way of modification. 200 patterns were then obtained by classification of each of the three items. It was found that many cases of modification in actual design fit 9 of the 200 patterns. It is possible that those 9 patterns can be exploited for computer support of modification process.